Targeted next-generation sequencing for genetic variants of left ventricular mass status among community-based adults in Taiwan - Fan, Hsien-Yu; Lin, Wan-Yu; Lu, Tzu-Pin; Chen, Yun-Yu; Hsu, Justin BoKai; Yu, Sung-Liang; Su, Ta-Chen; Lin, Hung-Ju; Chen, Yang-Ching; Chien, Kuo-Liong (Frontiers in Genetics, 2023)
Background: Left ventricular mass is a highly heritable disease. Previous studies have suggested that common genetic variants associated with left ventricular; however, the roles of rare variants were still unknown. We performed the targeted next generation sequencing by using the TruSight Cardio Panel, which can provide comprehensive coverage of 175 genes with known associations to 17 inherited cardiac conditions. Methods: We conducted the next-generation sequencing using the Illumina TruSight Cardiomyopathy Target Genes platform using the 5% and 95% extreme-values of left ventricular mass from the community-based participants. After removing poor quality of next-generation sequencing subjects, including call rate <98%, Mendelian errors, 144 participants were used for the analysis. We performed the downstream analysis, including quality control, alignment, coverage length, and annotation, and after setting filtering criteria as depth more than 60, we found that a total of 144 samples and 165 target genes for the further analysis. Results: Of the 12,287 autosomal variants, most variants had minor allele frequencies <1% (rare frequency), and variants had minor allele frequencies ranging from 1% to 5%. In the multi-allele variant analyses, sixteen loci in 15 genes were significant using the false discovery rate less than 0.1. In addition, the gene-based analyses using the continuous and binary outcomes showed that 3 genes (CASQ2, COL5A1, and FXN) were remained to be associated with left ventricular mass status. One single-nucleotide polymorphism (rs7538337) enriched for the CASQ2 gene expressed in aorta artery (p = 4.6×10-18); another single-nucleotide polymorphism (rs11103536) for the COL5A1 gene expressed in aorta artery (p = 2.0×10-9). Among the novel genes discovered, CASQ2, COL5A1, and FXN were within the protein-protein interaction network with known cardiovascular genes. Conclusions: We clearly demonstrated candidate genes were associated with the left ventricular mass. Further studies to characterize the target genes and variants for their functional mechanism are warranted.